2017
DOI: 10.1007/s11011-017-0016-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated restraint stress and WiFi signal exposure on behavior and oxidative stress in rats

Abstract: Today, due to technology development and aversive events of daily life, Human exposure to both radiofrequency and stress is unavoidable. This study investigated the co-exposure to repeated restraint stress and WiFi signal on cognitive function and oxidative stress in brain of male rats. Animals were divided into four groups: Control, WiFi-exposed, restrained and both WiFi-exposed and restrained groups. Each of WiFi exposure and restraint stress occurred 2 h (h)/day during 20 days. Subsequently, various tests w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 96 publications
1
12
0
Order By: Relevance
“…In these experiments, sham controls and prior training of the animals to the conditions of exposure are important. In addition to increased ROS production, a change in the anxiety behavior, but not in memory performance, was found after WiFi exposure of rats exposed in tubes, which was enhanced by the exposure [59,60].…”
Section: Assessment Of Emf-induced Oxidative Stress In the Nervous Systemmentioning
confidence: 95%
See 3 more Smart Citations
“…In these experiments, sham controls and prior training of the animals to the conditions of exposure are important. In addition to increased ROS production, a change in the anxiety behavior, but not in memory performance, was found after WiFi exposure of rats exposed in tubes, which was enhanced by the exposure [59,60].…”
Section: Assessment Of Emf-induced Oxidative Stress In the Nervous Systemmentioning
confidence: 95%
“…WiFi exposure of adult male Wistar rats alone or with physical constraint impaired the learning behavior and memory performance accompanied by an oxidative stress response in the brain. [59]. Albeit having some methodological shortcomings, the study by Asl et al also showed increased ROS and NO production in rats exposed to RF-EMF/WiFi (2450 MHz; 0.98 mW/cm 2 ) [50].…”
Section: Observations In Emf-exposed Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…In elementary schools or high school, the quality of STEM education should be related to motivation, attention, perception of time and stress. Based on our expertise in the field of the evaluation of bioeffects of Electromagnetic Field EMF (Mobile phone, WIFI, electronic equipment [1][2][3][4], we ought to control the time of exposure of our children to EMF in order to reduce stress and to enhance memorization and thinking leading to a boost of STEM knowledge.…”
Section: Mini Reviewmentioning
confidence: 99%